Pengaruh Kegiatan Penyuluhan Pertanian terhadap Tingkat Eksistensi Petani Muda di Kecamatan Pacet - Lili Sunarya; Tyas Retno Wulan; Lucie Setiana (Pascasarjana Universitas Jenderal Soedirman, 2022)
Farmer regeneration aims to increase agricultural competitiveness due to the aging of farmers towards the existence of young farmers. The results of the 2018 inter-census survey showed that young farmers aged less than 35 were 11.66%. This situation encourages the importance of finding solutions to realize the regeneration of farmers. This study describes the existence of young farmers through increasing agricultural extension activities and the role of the family. The analysis used in this study is multiple linear regression, and the sample in this study amounted to 90 young farmers. The purpose of the study was to determine the influence of the role of agricultural extension workers and the level of regeneration on the existence of young farmers in Kecamatan Pacet. The results showed that agricultural extension activities and the level of regeneration had a positive and significant influence on the presence of young farmers, meaning that young farmers needed support to take action or behavior for their farming activities; the existence of young farmers could not be separated from the role of farmers in general who motivated them by introducing the function—farmer groups to develop sustainable agriculture.